RARE EARTH ELEMENTS AND STABLE SULPHUR (?34S) ISOTOPE OF BARYTE MINERALIZATION IN LIJI AREA, NORTHERN BENUE TROUGH, NORTHEASTERN NIGERIA (Nigerian Journal of Technology, 2020)
The Liji area lithologically consists of inliers of granite and pegmatite members of the Pan-African granitoids surrounded by Cretaceous sedimentary deposits of Bima, Yolde, Pindiga and Gombe Formations. Epigenetic fracture-filling baryte mineralization hosted by granite, pegmatite and Bima Sandstone were delineated, sampled and analyzed for rare-earth elements (REEs) and stable sulphur isotope geochemistry. The REEs of the distal (unaltered) rocks indicated normal values (26.15-36.81 ppm) before mineralization was marked by enrichment of light rare-earth elements (LREEs) (27.94 ppm) relative to the heavy rare-earth elements (HREEs) (5.34 ppm) and negative Eu anomalies typical of calc-alkaline granites of Pan-African age. The baryte separates were marked by enriched LREEs and depleted HREEs with pronounced positive Eu anomalies indicating the invasion and consequent deposition of baryte-rich hydrothermal fluid under oxidizing conditions in the N-S and E-W striking fractures. Stable sulphur isotope of the baryte gives values that ranged from 18.3 - 19.8o/oo CDT indicating that the source of sulphur is from ocean water and not from magmatic, fresh water and connate water sources from the nearby granite, pegmatite and sandstone. http://dx.doi.org/10.4314/njt.v39i3.6